(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The thesis examines the conceptual directions of organizing a bank audit based on international auditing standards (IAS). The conceptual model of a bank audit is characterized as a combination of risk sensitivity, regulatory compliance, and information value.